Direct costs of Inflammatory bowel diseases in a Finnish tertiary-level clinic - Kosonen, Juuso; Rankala, Rasmus (fi=Turun yliopisto|en=University of Turku|, 2018)
Background Inflammatory bowel diseases (IBD), Crohn’s disease (CD) and ulcerative colitis (UC), are chronic diseases and associated with a high and continuous economic burden. The introduction of biological agents has changed the distribution of costs in last two decades and there were no recent studies of costs in a Finnish healthcare setting. The aim of this study was to estimate direct healthcare costs of these diseases in a tertiary-level clinic. Methods IBD patients visiting Turku University Hospital during a one-year period, who were living in a hospital district area and were over 18 years old, were selected in the study. This comprised a IBD group of 2208 patient, including 794 cases of Crohn’s disease and 1414 cases of ulcerative colitis. To gain more accurate data, age and sex matched control group was selected from patients who visited emergency department to represent the general population comparable to the IBD group. The data of the direct costs was collected from Turku Center of Clinical Informatics. Results IBD-generated direct costs in a tertiary-level clinic was estimated to be 3981€ per patient annually. IBD patient who was given infliximab generated 9157€ more direct healthcare costs annually compared to the IBD patient with no infliximab medication. CD patient generated 1111€ more direct healthcare costs annually than UC patient. Conclusion Our findings indicate that the total costs remain stable, but biological agents comprise of a hefty proportion of the costs. To further estimate the impact of biological agents with the introduction of biosimilars regarding cost-of-disease, more studies are required.